Pembrolizumab in Patients with Advanced Metastatic Germ Cell Tumors. (12th February 2021) - Tsimberidou, Apostolia-Maria; Vo, Henry Hiep; Subbiah, Vivek; Janku, Filip; Piha-Paul, Sarina; Yilmaz, Bulent; Gong, Jing; Naqvi, Mohammad Faraz; Tu, Shi-Ming; Campbell, Matthew; Meric-Bernstam, Funda; Naing, Aung
Abstract: Lessons Learned: Advanced germ cell tumors are aggressive and associated with poor prognosis. Pembrolizumab was overall well tolerated in 12 heavily pretreated patients. Three patients had radiographic stable disease that lasted for 10.9 months, 5.5 months, and 4.5 months, respectively. Published data of immunotherapeutic agents in patients with advanced germ cell tumors are confirmed. The limited antitumor activity of immunotherapy in germ cell tumors is, at least partially, attributed to tumor biology (low tumor mutational burden; low PD-1 expression) and other poor-risk features. Tumor profiling to understand the mechanisms of resistance to pembrolizumab and innovative clinical trials that may include immunotherapy are warranted. Background: Advanced germ cell tumors are associated with poor prognosis. We investigated the role of pembrolizumab in patients with advanced germ cell tumors. Methods: We analyzed a prespecified cohort of an open-label, phase II clinical trial in which patients with advanced germ cell tumors were treated with pembrolizumab (200 mg) intravenously every 21 days. The endpoints of the study were the non-progression rate (NPR) at 27 weeks, safety, and tolerability. An NPR >20% was considered successful and worthy of further pursuit. Results: From August 2016 to February 2018, 12 patients (10 men, 2 women) were treated (median age, 35 years [range, 22–63 years]; median number of prior systemic therapies, 3.5 [range, 2–7]; median number of metastatic sites, 3 [range, 2–8]). Overall, pembrolizumab was well tolerated. One patient experienced both grade 1 immune-related skin rash and grade 3 immune-related pneumonitis. No patient died from toxicity. Three patients had radiographic stable disease that lasted for 10.9 months, 5.5 months, and 4.5 months, respectively. No objective response was noted. The median progression-free survival was 2.4 months (95% confidence interval [CI], 1.5–4.5 months), and the median overall survival was 10.6 months (95% CI, 4.6–27.1 months). The 27-week NPR was 9.0% (95% CI, 0.23–41.2%). Conclusion: Overall, pembrolizumab was safe and had limited antitumor activity in these patients. In the advanced, metastatic setting, tumor profiling to understand the mechanisms of resistance to immunotherapy and innovative clinical trials to identify efficacious combination regimens rather than off-label use of pembrolizumab are warranted.